2013
DOI: 10.1371/journal.pone.0057901
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Genomic and Transcriptomic Analysis Reveals Potential Targets Associated with Cell Proliferation in Uterine Leiomyomas

Abstract: BackgroundUterine Leiomyomas (ULs) are the most common benign tumours affecting women of reproductive age. ULs represent a major problem in public health, as they are the main indication for hysterectomy. Approximately 40–50% of ULs have non-random cytogenetic abnormalities, and half of ULs may have copy number alterations (CNAs). Gene expression microarrays studies have demonstrated that cell proliferation genes act in response to growth factors and steroids. However, only a few genes mapping to CNAs regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…An unsupervised hierarchical clustering analysis using gene expression data previously published by our group (Cirilo et al, 2013) revealed one cluster enriched with MED12 mutated cases, in agreement with previous reports (Mehine et al, 2013). In contrast, HMGA2 expression had no influence on the clustering analysis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…An unsupervised hierarchical clustering analysis using gene expression data previously published by our group (Cirilo et al, 2013) revealed one cluster enriched with MED12 mutated cases, in agreement with previous reports (Mehine et al, 2013). In contrast, HMGA2 expression had no influence on the clustering analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Transcriptomic data (Two-Color Human GE 4×44K Microarrays, Agilent Technologies) from 42 UL from our previous study (Cirilo et al, 2013;data Table II).…”
Section: Gene Expression Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of genomic and transcriptomic analysis can be used to identify cancer-driver genes and disrupted pathways, which can be drug targetable [20]. This strategy has revealed functionally relevant drivers involved in the carcinogenic process in different tumor types, including oral carcinoma [21], ovarian cancer [22], penile carcinoma [23,24], uterine leiomyoma [25] and leiomyosarcoma [26].…”
Section: Introductionmentioning
confidence: 99%
“…The FA pathway has also been shown to be upregulated in infection such as HPV -infection [41] and BRCA1 appears to be localized to the cellular component of the centrosome. cancers revealed restricted expression of FANCA and BRCA1 genes [43] and these tumors exhibit dysfunction of centrosome [44]. The FANCD2-Ub can interact with PCNA proliferating cell nuclear antigen [34,44] and BRCA2/RAD51 functionally interacts with FANCD2 complex [45,46].…”
Section: Discussionmentioning
confidence: 99%